The subterranean Aenigmachanna gollum, a new genus and species of snakehead (Teleostei: Channidae) from Kerala, South India - Britz, Ralf; Anoop, V.k.; Dahanukar, Neelesh; Raghavan, Rajeev (Zootaxa, 2019)
Aenigmachanna gollum, new genus and species, is described from Kerala, South India. It is the first subterranean species of the family Channidae. It has numerous derived and unique characters, separating it from both the Asian Channa Scopoli and the African Parachanna Teugels & Daget. Uniquely among channids, A. gollum has a very slender (maximum body depth only 11.1–11.3% SL), eel-like body (head length 20.8–21.6% SL), large mouth (jaw length 60.4–61.1 % HL), 43–44 anal-fin rays, 83–85 scales in a lateral series, an unusual colour pattern and it lacks pored lateral-line scales on the body and body buoyancy. In addition, it is distinguished by its DNA barcode sequence, which is 15.8–24.2% divergent from other species of the family Channidae. Morphological modifications usually associated with a subterranean life, such as reduction of eyes and enhancement of non-visual senses (taste, smell, mechanosensory systems) are absent in A. gollum. However, it shares with subterranean fishes a slight reduction of its pigmentation in comparison to epigean channids.